2021
DOI: 10.1590/0102-311x00218320
|View full text |Cite
|
Sign up to set email alerts
|

Associação das condições sociais e econômicas com a incidência dos problemas com o sono durante a pandemia de COVID-19

Abstract: Resumo: O sono é importante para a manutenção da saúde física, emocional e para o bem-estar. Poucos estudos avaliaram o efeito das condições socioeconômicas no sono no período da COVID-19. O objetivo foi analisar o aumento ou a incidência dos problemas do sono segundo condições demográficas e econômicas, prévias à pandemia, e segundo mudanças nas condições financeiras, ocupacionais e tarefas domésticas durante a pandemia. Estudo realizado via web, usando dados de 24 de abril a 24 de maio, com 45.160 brasileiro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
18

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 35 publications
2
9
0
18
Order By: Relevance
“…This study also showed that sleep alterations are common in mothers of children/adolescents with SCD, in view of the concern and fear surrounding COVID-19 that permeates their experiences. Quality of sleep tends to be deteriorated as a result of the impacts caused by social distancing, along with the fear of acquiring the disease and exposure to recurrent news reports of the pandemic 14 . In the context of social isolation in the context of social isolation, sleep problems during a pandemic are due to the introduction of several stressors, including loneliness due to social isolation, fear of contracting the disease, socioeconomic problems and uncertainty about the future 15 .…”
Section: Discussionmentioning
confidence: 99%
“…This study also showed that sleep alterations are common in mothers of children/adolescents with SCD, in view of the concern and fear surrounding COVID-19 that permeates their experiences. Quality of sleep tends to be deteriorated as a result of the impacts caused by social distancing, along with the fear of acquiring the disease and exposure to recurrent news reports of the pandemic 14 . In the context of social isolation in the context of social isolation, sleep problems during a pandemic are due to the introduction of several stressors, including loneliness due to social isolation, fear of contracting the disease, socioeconomic problems and uncertainty about the future 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Não somente a preocupação com a falta de comida, mas também o aumento do desemprego, a diminuição da renda, o isolamento social, hábitos alimentares não saudáveis, aumento no uso de telas, violência doméstica e sedentarismo, influenciam para que a população ficassem mais predispostas a desenvolver transtornos mentais (Guerra et al, 2018;Almeida et al, 2020;Cazal et al, 2021;Romero et al, 2021). Isso reflete também no sono, como foi demonstrado por Lima et al (2021), os quais identificaram que os problemas com sono eram mais frequentes em pessoas que tiveram alteração em sua renda, em mulheres e em jovens.…”
Section: Saúde Mentalunclassified
“…Idosos com sintomas depressivos e nível elevado de estresse também apresentam maior dificuldade para dormir. Além do mais, pessoas com rendimentos financeiros menores, no período prépandêmico, foram mais propensas a apresentar dificuldade com o sono devido a preocupação e ansiedade gerados pela incerteza econômica do período de isolamento social (Lima, et al, 2021;Barros et al, 2020;Iroldi et al, 2020). também exerce efeito imunomodulador.…”
Section: Saúde Física X Mentalunclassified